ENERGY AUDIT AND ENERGY MANAGEMENT IN THE SUGAR INDUSTRY - Soppimath, Vishwanath M; Hudedmani, Mallikarjun G (MATTER: International Journal of Science and Technology, 2017)
Energy audit plays a vital role in deciding energy conservation practices. The systematic and scientific way of use of electrical energy is guaranteed. Electricity is playing a crucial role in everybody’s life alternatively, energy usage index indicate the country’s economy, growth and standard of living. In contrast to this increasing energy demands and prices are alarming greatly and retarding overall growth. Energy audit provides a solution to reduce the consumption of energy. Energy audit is the beginning of energy management program which report the possible opportunities. The energy audit projects the possible conservation opportunities in enhancing the energy efficiency of the system considering and not limited to electrical, thermal and other areas of a system where energy is involved. About 35 to 45 % of conservation potential in the existing industrial sector is noticed. This clearly brings out the need for efficient machines and mechanisms to be manufactured to reduce the burden on the energy systems when in service considering the cost and efficiency.